Biofilms in bioelectrochemical systems : from laboratory practice to data interpretation - Beyenal, H.; Babauta, Jerome T. (Hoboken : Wiley, 2015)
'This book serves as a manual of research techniques for electrochemically active biofilm research. Using examples from real biofilm research to illustrate the techniques used for electrochemically active biofilms, this book is of most use to researchers and educators studying microbial fuel cell and bioelectrochemical systems. The book emphasizes the theoretical principles of bioelectrochemistry, experimental procedures and tools useful in quantifying electron transfer processes in biofilms, and mathematical modeling of electron transfer in biofilms. It is divided into three sections: Biofilms: Microbiology and microbioelectrochemistry - Focuses on the microbiologic aspect of electrochemically active biofilms and details the key points of biofilm preparation and electrochemical measurement. Electrochemical techniques to study electron transfer processes - Focuses on electrochemical characterization and data interpretation, highlighting key factors in the experimental procedures that affect reproducibility. Applications - Focuses on applications of electrochemically active biofilms and development of custom tools to study electrochemically active biofilms. Chapters detail how to build the reactors for applications and measure parameters.'--
Includes index.
Machine generated contents note: 1. Introduction to electrochemically active biofilms H Beyenal and J. Babauta 2. Theoretical and practical considerations for culturing Geobacter biofilms in microbial fuel cells and other bioelectrochemical systems Allison M. Speers and Gemma Reguera 3. Microbial Community Characterization on Polarized Electrode Surfaces John Regan 4. Characterization of Electrode-Associated Biomass and Microbial Communities Shino Suzuki, Shun'ichi Ishii and Orianna Bretschger 5. Biofilm electrochemistry J. Babauta and H. Beyenal 6. Theory of Redox Conduction and the Measurement of Electron Transport Rates through Electrochemically Active Biofilm Darryl A. Boyd, Jeffrey S. Erickson, Jared N. Roy, Rachel M. Snider, Sarah M. Strycharz-Glaven, and Leonard M. Tender 7. Electronic Conductivity in Living Biofilms: Physical Meaning, Mechanisms and Measurement Methods Nikhil S. Malvankar and Derek R. Lovley 8. Electrochemical Impedance Spectroscopy as a Powerful Analytical Tool for the Study of Microbial Electrochemical Cells Rachel A. Yoho, Sudeep C. Popat, Francisco Fabregat-Santiago, Sixto Gimenez, Annemiek ter Heijne, and Cesar I. Torres 9. Modeling Electron transfer processes in biofilms Ryan Renslow, Jerome Babauta, Andrew Kuprat, Jim Schenk, Cornelius Ivory, Jim Fredrickson, and Haluk Beyenal 10. Applications of Bioelectrochemical Energy Harvesting in the Marine Environment Clare E. Reimers 11. Large Scale Benthic Microbial Fuel Cell Construction, Deployment, and Operation Jeff Kagan, Lewis Hsu, and Bart Chadwick .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Fuel cells -- Materials; Energy harvesting; Biofilms -- Industrial applications; Bioelectrochemistry -- Industrial applications; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Bioelectrochemistry - Industrial applications; Electronic books; Electronic books